Controlled flexibility of porous coordination polymers by shifting the position of the –CH3 group around coordination sites and their highly efficient gas separation. Issue 8 (1st May 2018) - Duan, Jingui; Zhang, Qiang; Wang, Suna; Zhou, Bihang; Sun, Jiajia; Jin, Wanqin
Abstract : By adjusting the position of the methyl group, we found significant changes in the structural flexibility of the obtained PCPs, which also showed good gas separation ability. Abstract : As an emerging class of crystalline materials, porous coordination polymers (PCPs) with regular and flexible nanopores have become particularly promising for adsorption applications. Here, we report a new method to synthesize PCPs with varied flexibility by shifting the position of the methyl group, the shortest alkyl chain, around the coordination sites of T-shaped ligands of H2 NL 1 (5-(2′-methyl-imidazol-1-yl)-isophthalic acid) and H2 NL 2 (5-(4′-methyl- imidazol-1-yl)-isophthalic acid). The two generated PCPs (NTU-40 and NTU-41) showed a significant change in gate opening pressure ( P / P 0 : 0.25 to 0.0001) under the stimulus of N2 at 77 K. In addition, the square window (5 × 5 Å 2 ) of the one-dimensional (1D) zigzag channel was divided into two small triangular and straight channels in NTU-41. More importantly, the synergistic effect of structural flexibility, channel type and the micro-pores enabled highly efficient CO2 /CH4 and C2 H4 /CH4 separation under both equilibrium state and dynamic conditions, as well as having good potential for challenging C2 H4 /C2 H6 separation.